1996
DOI: 10.1046/j.1471-4159.1996.67031005.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pituitary Adenylate Cyclase‐Activating Polypeptide 38 (PACAP38)‐, PACAP27‐, and Vasoactive Intestinal Peptide‐Stimulated Responses in N1E‐115 Neuroblastoma Cells

Abstract: In this study, the effects of three related peptides, pituitary adenylate cyclase‐activating polypeptide 38 (PACAP38), PACAP27, and vasoactive intestinal peptide (VIP), on cyclic AMP (cAMP) accumulation and intracellular Ca2+ concentration ([Ca2+]i) were compared in N1E‐115 cells. PACAP38 and PACAP27 stimulated cAMP accumulation up to 60‐fold with EC50 values of 0.54 and 0.067 nM, respectively. The effect of VIP on cAMP accumulation was less potent. The binding of 125I‐PACAP27 to intact cells was inhibited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In 1994, Arimura and colleagues determined that PACAP immunoreactivity and PACAP‐preferring (PAC 1 ) binding sites could be detected in extracts of the developing rat brain on embryonic day (E) 14, a time of peak neurogenesis 1. Others had shown that PACAP can regulate the proliferation and differentiation of neuroblastoma cells in vitro 2–4. More recently, DiCicco‐Bloom and colleagues showed that cultured cortical neuroblasts isolated from the rat at E 13.5 respond to PACAP with decreased DNA synthesis, enhanced neurite outgrowth, and increased trkB expression 5.…”
Section: Localized Expression Of the Pacap Ligand/receptor Signaling mentioning
confidence: 99%
“…In 1994, Arimura and colleagues determined that PACAP immunoreactivity and PACAP‐preferring (PAC 1 ) binding sites could be detected in extracts of the developing rat brain on embryonic day (E) 14, a time of peak neurogenesis 1. Others had shown that PACAP can regulate the proliferation and differentiation of neuroblastoma cells in vitro 2–4. More recently, DiCicco‐Bloom and colleagues showed that cultured cortical neuroblasts isolated from the rat at E 13.5 respond to PACAP with decreased DNA synthesis, enhanced neurite outgrowth, and increased trkB expression 5.…”
Section: Localized Expression Of the Pacap Ligand/receptor Signaling mentioning
confidence: 99%